Effect of topical motesanib in experimental corneal neovascularization model - Celenk, Mukaddes; Yildirim, Hakan; Tektemur, Ahmet; Balbaba, Mehmet; Erdag, Murat (Springer, 2023)
PurposeThis study aimed to compare the efficacy of topical bevacizumab and motesanib in an experimental corneal neovascularization model, and find the most effective motesanib dose.Materials and methodsIn experiments, 42 Wistar Albino rats were randomly divided into six groups (n = 7). Corneal cauterization was applied to all groups except the group 1. Group 1 did not receive any treatment. Topical dimethylsulfoxide was applied to sham group three times a day(tid). Topical bevacizumab drops (5 mg/ml) were applied to Group 3 tid. Topical motesanib drops with a dose of 2.5, 5, and 7.5 mg/ml were respectively applied in Groups 4, 5, and 6 tid. On the 8th day, corneal photographs of all rats were taken under general anesthesia, and the percentage of corneal neovascular area was calculated. VEGF-A mRNA, VEGFR-2 mRNA, miRNA-21, miRNA-27a, miRNA-31, miRNA-126, miRNA-184, and miRNA-204 were evaluated by the qRT-PCR method in corneas taken after decapitation.ResultsThe percentage of corneal neovascularization areas and VEGF-A mRNA expression levels were decreased in all treatment groups compared to group 2 (p < 0.05). VEGFR-2 mRNA levels were found to be statistically significantly decreased in groups 4 and 6 compared to group 2 (p < 0.05). Statistically significant changes were detected in the expression levels of only miRNA-126 among all miRNAs.ConclusionMotesanib with a dose of 7.5 mg/ml statistically significantly suppressed the VEGFR-2 mRNA level compared with other treatment doses and may be more effective than bevacizumab. Further, miRNA-126 can be used as a proangiogenic marker.
Keywords: Corneal neovascularization; Bevacizumab; Motesanib; Quantitative real-time polymerase chain reaction (qRT-PCR)